Determinants of Aesthetic Preference for Product Metaphors. (July 2014) - Cila, Nazli; Borsboom, Frank; Hekkert, Paul
To generate a product metaphor, designers have to come up with a metaphorical association between a target and a source, and then apply this association to physical form. In this article, we address the interplay between novelty and understandability of a metaphorical association, and subtlety and identifiability of metaphor application, via two studies conducted to investigate how these four factors affect aesthetic preference for product metaphors. In Study 1, it was shown that these four factors jointly explain the preference, but each factor suppresses the effect of its counterpart. Direct correlations between variables and aesthetic preference were only moderate or not significant, but each relationship became significant when the influence of the other factor was statistically controlled for. Study 2 focused on the application component of a metaphor by systematically manipulating the factors of subtlety and identifiability in the design of two product metaphors. It was again shown that these factors together explain aesthetic preference: metaphors that maximize identifiability and subtlety were found to be most aesthetically pleasing. In combination, these studies demonstrate that the aesthetic quality of product metaphors results from simultaneously maximizing clarity (i.e., the metaphor is understandable and identifiable) and interestingness (i.e., the metaphor is novel and its application subtle) at the association and application levels. This finding is discussed in light of a "dual impulses" model of aesthetic preference.